More Gamer, Less Girl: Gendered Boundaries, Tokenism, and the Cultural Persistence of Masculine Dominance - Drenten, Jenna; Harrison, Robert L; Pendarvis, Nicholas J (Journal of Consumer Research, 2023)
Abstract How do exclusionary boundaries persist in consumption subcultures amid increased progress, representation, and inclusion? In video gaming, women have come to represent nearly half of the market; yet, this is a limited indicator of gender-based progress. A culture of masculine dominance persists. Extending previous research on boundary work, the authors employ a cultural perspective of tokenism to examine how gendered boundaries in consumption subcultures persist despite efforts to transform or even eradicate them. This qualitative study draws on interviews with 23 gamers who identify as women (ages 19–29 years), coupled with data from social media platforms, news media, and industry reports. Empirical findings capture the recursive process of maladaptive boundary crossing: how women’s efforts to subvert gendered boundaries at the micro level (e.g., through response enactments) get churned through the structuring tokenistic mechanics of boundary work at the meso level and result in the inadvertent cultural persistence of masculine dominance. The analysis offers a conceptual framework that explains how micro–meso level dynamics perpetuate and conceal inequity in consumption subcultures. Implications address the precarious promise of progress and the cultural legacy of tokenism in the marketplace with particular relevance to broader systems of domination.